Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1055/a-1393-6668
|View full text |Cite
|
Sign up to set email alerts
|

Risk to Radiology Staff for Occupational COVID-19 Infection in a High-Risk and a Low-Risk Region in Germany: Lessons from the “First Wave”

Abstract: Purpose The recent COVID-19 pandemic has resulted in an increasing overload of the medical system. Healthcare workers (HCW) in radiology departments are exposed to a high infection risk similar to HCWs in the ICU or dedicated COVID wards. The goal of our paper is to evaluate the prevalence of IgG antibody against SARS-CoV-2 among radiology HCWs in two different hospitals and regions in Germany with a low and high COVID-19 prevalence and to compare it to the prevalence in other clinical personnel. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
0
7
0
4
Order By: Relevance
“…The dose-response dependence (at a direct contact with the patient or at contact with excretions of the organism) also was noted (Chou et al 2020). Researchers from Germany found that healthcare workers in radiology departments had high hazard of occupational infection, similar to the healthcare workers in intensive care units and specialized COVID-19 units (Finkenzeller et al 2021).…”
Section: Discussionmentioning
confidence: 94%
“…The dose-response dependence (at a direct contact with the patient or at contact with excretions of the organism) also was noted (Chou et al 2020). Researchers from Germany found that healthcare workers in radiology departments had high hazard of occupational infection, similar to the healthcare workers in intensive care units and specialized COVID-19 units (Finkenzeller et al 2021).…”
Section: Discussionmentioning
confidence: 94%
“…Employees in radiology departments are at an increased risk of SARS-CoV-2 infection, similar to those working in intensive care units and dedicated COVID-19 units 90 . Due to the limited scope of this overview, please refer to the relevant specialized literature for more detailed information regarding these risks and possible protective measures.…”
Section: Risk Of Covid-19 For Personnel In Radiologymentioning
confidence: 99%
“…Mitarbeiterinnen und Mitarbeiter radiologischer Einrichtungen haben ein erhöhtes Risiko, sich mit SARS-CoV-2 zu infizierten – ähnlich dem von Beschäftigten auf Intensiv- oder dedizierten COVID-19-Stationen 90 . Genauere Erläuterungen dieser Risiken und möglicher Schutzmaßnahmen müssen aufgrund des begrenzten Rahmens dieser Übersichtsarbeit ebenfalls entsprechender Spezialliteratur vorbehalten bleiben.…”
Section: Risiko Von Covid-19 Für Radiologisches Personalunclassified
“…Neben den Einschränkungen im öffentlichen Leben waren medizinische Einrichtungen angehalten, nicht zwingend notwendige, planbare Aufnahmen und Operationen zu verschieben und damit Behandlungs- und Intensivkapazitäten in den Kliniken für potenzielle COVID-19-Erkrankte vorzuhalten 1 . Darüber hinaus waren verschiedenste Anpassungen der Arbeitsabläufe erforderlich, beispielsweise veränderte Kommunikations- und Personalstrukturen sowie Hygienemaßnahmen, um den Behandlungsbedarf von Patienten aufrecht zu erhalten sowie den Schutz der Mitarbeitenden zu gewährleisten 2 .…”
Section: Introductionunclassified
“…In addition to the limitations placed on public life, medical facilities had to postpone any elective, non-essential imaging and procedures in order to ensure intensive care capacity and capacity for the treatment of potential COVID-19 patients in hospitals [1]. Moreover, a wide range of adjustments had to be made to workflows, e. g., changed communication and personnel structures and hygiene measures, in order to meet the treatment needs of patients and to ensure employee safety [2].…”
Section: Introductionmentioning
confidence: 99%